2018
DOI: 10.1111/nyas.13605
|View full text |Cite
|
Sign up to set email alerts
|

Opioid and nondopamine reward circuitry and state‐dependent mechanisms

Abstract: A common notion is that essentially all addictive drugs, including opioids, activate dopaminergic pathways in the brain reward system, and the inappropriate use of such drugs induces drug dependence. However, an opioid reward response is reportedly still observed in several models of dopamine depletion, including in animals that are treated with dopamine blockers, animals that are subjected to dopaminergic neuron lesions, and dopamine-deficient mice. The intracranial self-stimulation response is enhanced by st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 126 publications
(127 reference statements)
1
6
0
Order By: Relevance
“…But previous study finding also suggests that DA independent opioid reward is possibly observed in opioid‐naive states, but not in opioid‐dependent states . A recent study has further shown that the self‐stimulation response of the brain is increased by stimulants but reduced by morphine, suggesting that opioid dependence may change the GABA neurons from inhibitory to excitatory function, resulting in disappearance of DA independent opioid reward pathway . These study findings confirm that DA neurotransmission may not always be required for opioid reward responses in AUD patients …”
Section: Putative Mechanisms Of Action Implicated In Drugs With Anticsupporting
confidence: 71%
See 2 more Smart Citations
“…But previous study finding also suggests that DA independent opioid reward is possibly observed in opioid‐naive states, but not in opioid‐dependent states . A recent study has further shown that the self‐stimulation response of the brain is increased by stimulants but reduced by morphine, suggesting that opioid dependence may change the GABA neurons from inhibitory to excitatory function, resulting in disappearance of DA independent opioid reward pathway . These study findings confirm that DA neurotransmission may not always be required for opioid reward responses in AUD patients …”
Section: Putative Mechanisms Of Action Implicated In Drugs With Anticsupporting
confidence: 71%
“…Opioids are referred to products that are extracted from plants or synthesized compounds (e.g., heroin, morphine, and oxycodone), and endogenous ligands include endomorphin, endorphin, enkephalins (Leu and Met), and dynorphin . Through three subtypes—μ (mu), δ (delta), and κ (kappa)—of G protein‐coupled opioid receptors, opioids produce inhibitory effects on downstream neurons when activated by endogenous ligands or synthetic receptor agonists . The binding affinity of those endogenous ligands depends on different receptor subtypes …”
Section: Putative Mechanisms Of Action Implicated In Drugs With Anticmentioning
confidence: 99%
See 1 more Smart Citation
“…We encourage clinicians to research and understand the importance of a molecular framework to explain the current underpinnings of endorphinergic/dopaminergic mechanisms related to opioid deficiency syndrome and a generalized reward processing deficiency [19,[78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97]. Along these same lines, many RDS subtypes have also been linked to hypodopaminergia using sophisticated imaging techniques [98][99][100][101][102][103][104][105][106][107][108][109][110][111][112].…”
Section: Discussionmentioning
confidence: 98%
“…While controversial, we allow that GPNs may confer a dose-dependent increase in limbic-region extracellular GABA-ergic activity [5][6][7], which in vulnerable individuals could indeed lead to ''liking'', misuse, and abuse and, in some cases, even to ''wanting'' (to use Berridge and Robinson's wellaccepted framework for addiction) and dependence [8]. And in keeping with the theme of appreciating the increased risk of abuse (with potential addiction) in opioid-or other polysubstance-addicted individuals, GABAergism may ''fast-track'' (i.e., via ''primed circuitry'') even weak GABA-mimetic agents such as GPNs to a place of ''want'' [9]; currently argued to be the decisive (psychological) factor in the development of addiction.…”
Section: Association Does Not Equal Causality (Or Innocent Until Promentioning
confidence: 99%